The role of resilience and readiness to change on students’ learning interest: E-learning implementation during Covid-19 - Harlina Nurtjahjanti; Anggun Resdasari Prasetyo; Lusi Nur Ardhiani (Jurnal Cakrawala Pendidikan, 2021)
COVID-19 affects the learning system at university. This study aims to determine the relationship between resilience and readiness for changes in students’ interest to learn in the Faculty of Psychology, Universitas Diponegoro, Indonesia, under the implementation of an e-learning system during the COVID-19 pandemic. The subjects in this study were 190 Students (M = 37, F = 153). The sampling technique used was cluster random sampling. The instruments used were the CD-RISC (16 items; α = .886), readiness for change questionnare (28 items; α = .919), and interest in leaning questionnare (14 items; α = .882). The multiple regression analysis show that there was a positive and significant correlation between resilience and interest in learning (r = .555; p .001), and a positive and significant correlation between readiness for change and interest in learning (r = .580; p .001). Furthermore, resilience and readiness for change together can predict students’ interest in learning during e-learning implementation (r = .675, p .001), R2 = .456, F = 78,294; p .001). Resilience and readiness for change effectively contributed 45.6% to predicting students’ interest in learning. These results suggest that students have resilience and readiness for change so that their interest in learning remains high despite having to face uncertain situation.